Effects of hydro-alcohol extract of mistletoe leaves on changes in body-weight, uterus-weight, right ovary and liver in female rats - Gbaranor, Barinua K.; Alasia, Onisojime M.; Tee, Popnen G.; Nonju, Tamunobarabiye I.; Austin-Asomeji, Iyingiala; Nonju, Imaobong I.; Nmehielle, Ihundah; Bademosi, Adetomi; Enebeli, Sarah K.; Edward, Ucheawaji F.; Nnoka, Valentime N.; Woha, Boobondah J. (International Journal of Research in Medical Sciences, 2022)
Background: Most people across rural areas in Africa depends of phytomedicine for the treatment of various diseases. This study aims to evaluate the impact of hydro-alcohol extract of mistletoe leaves on changes in body-weight, uterus-weight, ovary and liver of female Wistar rats. Methods: Forty-nine female rats were randomly selected into nine groups with five rats per group. Group 1 received 5 ml/kg of water, group 2 received mono sodium glutamate (MSG) 800 mg/kg, group 3 received extract 100 mg/kg, group 4 received extract 200 mg/kg, group 5 received extract 400 mg/kg, group 6 received extract 100 mg/kgand MSG 800 mg/kg, group 7 received extract 200 mg/kgand MSG 800vmg/kg, group 8 received extract 400 mg/kg and MSG 800 mg/kg and group 9 received letrozole 0.6 mg/kg and MSG 800 mg/kg. Administration of extract was done for 28 days. Results: Findings from the study revealed significance decreased in the final weight of the animals. When treated groups received extract “100 mg/kg, extract 200 mg/kg, extract 400 mg/kg, and extract 200 mg/kg and MSG 800 mg/kg”, it shows significance decreased in body weight difference. The results also show significance increased in the weight of the right ovary in the treated groups extract 100 mg/kg, extract 100 mg/kg and MSG 800 mg/kg. Extract 100 mg/kg, extract 400 mg/kg and MSG 800 mg/kg and letrozole 0.6 mg/kg and MSG 800 mg/kg, shows significance decreased in the weight of the uterus. MSG 800 mg/kg, “extract 100 mg/kg, extract 200 mg/kg, and extract 400 mg/kg”, it shows significance decreased in the weight of the liver. Statistical analysis was done using statistical package for the social sciences (SPSS) version 23 and p<0.05 was significant. Conclusions: There was significance decreased in rat’s body weight and significant increase in the right ovary when a lower dose of the extract was given and this increase could be due to MSG. The uterus significantly decreases when low dose of the extract was administered and the liver organ also has significant decreased in all the groups treated with extract alone.